Cost-reduction innovation under mixed economy - Pu-Yan Nie; Yong-Cong Yang (Kiel Institute for the World Economy (IfW), 2015)
Industries with mixed oligopoly are exceedingly popular all over the world, especially in developing countries, such as China. This paper highlights the innovation strategies of mixed duopoly with a (semi-) public firm and another private firm, and the effects of mixed oligopoly on innovation are captured. Firstly, the (semi-) public firm innovates more and produces more than the private firm. Secondly, the degree of the public ownership stimulates the output and innovation. Finally, the price difference and the price dispersion all increase with the degree of the public ownership under independent goods.
Keywords: C61; C72; D43; L13; 330; innovation; industrial organization; mixed duopoly; game theory